Simulation of Interference Effects of UWB Pulse Signal to the GPS Receiver - Xin Huang; Yazhou Chen; Yuming Wang (Discrete Dynamics in Nature and Society)
Ultra-wideband (UWB) pulse signal has an extremely narrow pulse width and wide frequency bandwidth, which overlaps with the operating frequency band of Global Position System (GPS) receivers, posing a potential threat to their performance. In response to this problem, through mathematical analysis and software simulation, the effects of UWB pulse signal under time-hopping-pulse position modulation (TH-PPM) on the performance of GPS receivers were studied. First, the expression and waveform of the UWB pulse signal were analyzed in the time-frequency domain, and it is concluded that the pulse repetition frequency (PRF) mainly affects the discrete spectrum of the UWB signal and the TH code period mainly affects the continuous spectrum. On this basis, the simulation on the power spectral density (PSD) of GPS signal and UWB signal under different pulse parameters was represented, from which a conclusion can be drawn that the PRF is the main factor impacting the PSD of the GPS signal. Furthermore, this paper analyzed the degradation of GPS receiver equivalent carrier-to-noise ratio (C/N0) and C/A code demodulation bit error rate (BER) under UWB interference, which are the crucial evaluating indicators of GPS signal quality. Eventually, we theoretically calculated the minimum interference level of the UWB interference signal to the GPS receiver, providing a theoretical reference for reducing the interference effects of UWB pulse signal on the performance of GPS receivers.